2005
DOI: 10.1038/nature03464
|View full text |Cite
|
Sign up to set email alerts
|

IRF-7 is the master regulator of type-I interferon-dependent immune responses

Abstract: The type-I interferon (IFN-alpha/beta) response is critical to immunity against viruses and can be triggered in many cell types by cytosolic detection of viral infection, or in differentiated plasmacytoid dendritic cells by the Toll-like receptor 9 (TLR9) subfamily, which generates signals via the adaptor MyD88 to elicit robust IFN induction. Using mice deficient in the Irf7 gene (Irf7-/- mice), we show that the transcription factor IRF-7 is essential for the induction of IFN-alpha/beta genes via the virus-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

109
1,994
9
12

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,983 publications
(2,149 citation statements)
references
References 30 publications
109
1,994
9
12
Order By: Relevance
“…TLR9 agonists (e.g. type B CpG DNA) stimulate robust IFN-b induction in myeloid DC and macrophages through MyD88 and IRF-1 independently of IRF3 or IRF7 [12,41]. Lack of synergy with the TLR9 agonist is consistent with specificity of IFN-b synergy for the IRF3 activating pathways.…”
Section: Discussionmentioning
confidence: 67%
“…TLR9 agonists (e.g. type B CpG DNA) stimulate robust IFN-b induction in myeloid DC and macrophages through MyD88 and IRF-1 independently of IRF3 or IRF7 [12,41]. Lack of synergy with the TLR9 agonist is consistent with specificity of IFN-b synergy for the IRF3 activating pathways.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, in plasmacytoid DCs, IRF7 is the key regulator of type I IFN production. This has been confirmed recently with the generation of mice deficient in the Irf7 gene [60]. Plasmacytoid DCs derived from these mice are completely non-responsive to TLR7 and TLR9 ligands with respect to induction of IFN-a, whereas induction is normal in plasmacytoid DCs from IRF3-deficient mice.…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 69%
“…CaIRF-7 should have different recognition motifs because two of six tryptophans are substituted in IRF-7 compared with CaIRF-1 and CaIRF-2. Though human IRF-7 is found as multiple forms (Lin et al, 2000;Honda et al, 2005), splicing variant of IRF-7 have not been found and isolated in teleosts.…”
Section: Discussionmentioning
confidence: 99%
“…According to IRF-1 and IRF-2 crystal structure in mouse (Escalante et al, 1998;Fujii et al, 1999), tertiary structures of predicted CaIRF-1 and CaIRF-2 DBD models consist of three ␣-helixes (␣1-␣3) with four stranded ␤-sheets (␤1-␤4) and three long loops (L1-L3), suggesting that these consistent elements should have uniform functions and recognize similar sequences. There is a lack of knowledge in teleosts with respect to IRF-7 which is the master regulator of type I IFN-dependent immune responses in mammals (Honda et al, 2005). CaIRF-7 gene consists of 10 exons and 9 introns, and lacks intron in 5 UTR that presents to human IRF-7a gene.…”
Section: Discussionmentioning
confidence: 99%